Relationship Between Postpartum Health Care With Contraceptive After Childbirth In Indonesia - Arantika Meidya Pratiwi (Alma Ata University Press, 2018)
Result of SDKI 2012 show that MMR in Indonesia is 359 deaths per 100,000 live births. This result show that Indonesia still far from the target SDGs (Suitable Development Goals), who reducing the Maternal Mortality Rate (MMR) to 70 per 100,000 live birth. One of the breakthrough programs of the Ministry of Health in an effort to accelerate the reduction in maternal mortality is to increase contraceptive after childbirth. The coverage of contraceptive after childbirth in Indonesia is still far from what is expected, from the 2013 Riskesdas data the coverage of contraceptive after childbirth in Indonesia was only 59.6%. Papua became a province with the lowest coverage of only 26%. The purpose of this study was to determine the relationship between postpartum health care and contraceptive after childbirth in Indonesia. This study using secondary data from